Recording microindentation and adhesion tests to analyse the depth-dependent mechanical and adhesive properties of multilayer polymer films as shown for gelatine-coated polyethylene terephthalate and polyethylene films. (January 2021) - Lach, Ralf; Richter, Sandra; Heilmann, Andreas; Grellmann, Wolfgang
Further developed methods based on an indenter penetration into a material allow generalised quantitative statements on the composition, the depth-dependent mechanical properties and the delamination behaviour of multilayer polymer films, which is demonstrated on gelatine-coated polyethylene terephthalate and polyethylene films. These highly sensitive polymer testing methods, include the recording microindentation test and the recording adhesion test, describe the material behaviour multi-parametrically and are fast (raw data acquisition within several minutes) and relatively simple, requiring a minimum 1 gram sample depending on the film thickness. Based on the Vickers hardness under load approach, the hardness–depth diagrams calculated from the recording microindentation test provide information about the structure, the thickness and the coating hardness and the substrates. The tangential load vs. tangential path length diagrams from recording adhesion test can detect different scratch processes such as continuous scratching or non-continuous stick-slip layer delamination. Furthermore, they form the basis to quantitatively analyze adhesion, i.e. to determine the critical tangential load and the critical tangential delamination work. Both are highly dependent on the substrate type and treatment.